Physical And Chemical Characterization Of Malaysian Sulphide Gold Ore From East Peninsular Malaysia - Mohamad Muzaffar, Hud (Universiti Sains Malaysia, 2018)
The sulphide ore samples are obtained from the High Grade Sulphide Ore stockpile at Selinsing Gold Mine, Pahang. The method used on the site is grab sampling by taking about 25-30 randomly chosen spots, below ½ of the stockpile height. The samples are divided into bulk sample and 5 sieve size fractions: 90µm, 75µm, 50µm, 38µm and -38µm. Both bulk sample and the 5 size fractions were characterized using X-Ray Fluorescence (XRF) and X-Ray Diffraction (XRD). The ore samples primarily compose of quartz and K-feldspar (microcline). The main sulphide minerals arechalcopyrite, stibnite, pyrrhotite and arsenopyrites. Bulk sample are subjected to fire assay analysis, direct cyanide leaching and morphological study using optical microscope and SEM/EDX of polish section. The gold was found associated with arsenopyrite, stibnite and quartz. The head grade was found to be in the range of 0.954 g/T based on fire assay result while direct cyanide leaching gives 83% recovery indicates that the sulphide ore sample can be classified as partly refractory.